2021
DOI: 10.3389/fonc.2021.724692
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Alterations in Lung Adenocarcinoma With Ground-Glass Nodules: A Systematic Review and Meta-Analysis

Abstract: Background and AimsNodular ground-glass lesions have become increasingly common with the increased use of computed tomography (CT), while the genomic features of ground-glass opacities (GGOs) remain unclear. This study aims to comprehensively investigate the molecular alterations of GGOs and their correlation with radiological progression.MethodsStudies from PubMed, Embase, Cochrane Library, and Web of Science, using PCR, targeted panel sequencing, whole exosome sequencing, and immunohistochemistry, and report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…observed that PD-L1 expression levels were similar in GGO-LUAD, SN-LUAD, different pathological subtypes, and multiple primary lung ADC ( 16 ). However, a meta-analysis revealed that PD-L1 expression in GGO was significantly lower than in SN ( 34 ). Furthermore, PD-L1 expression is higher in SN nodules than in PNS nodules, suggesting that immune checkpoint adjustment occurs in aggressive nodules ( 17 ).…”
Section: Other Molecular Features Of Ggnsmentioning
confidence: 99%
“…observed that PD-L1 expression levels were similar in GGO-LUAD, SN-LUAD, different pathological subtypes, and multiple primary lung ADC ( 16 ). However, a meta-analysis revealed that PD-L1 expression in GGO was significantly lower than in SN ( 34 ). Furthermore, PD-L1 expression is higher in SN nodules than in PNS nodules, suggesting that immune checkpoint adjustment occurs in aggressive nodules ( 17 ).…”
Section: Other Molecular Features Of Ggnsmentioning
confidence: 99%
“…The differences in EGFR mutation frequency among these studies may be partly explained by differences in study populations (Asian vs. Caucasian), detection methods (polymerase chain reaction vs. next generation sequencing), and nodule subtypes (pure GGNs vs. PSNs). Other genetic alterations identified in lung adenocarcinoma manifesting as SSNs included KRAS mutations, HER2 mutations, BRAF mutations, ALK rearrangement, and ROS1 rearrangement ( 11 , 53 - 58 ).…”
Section: Genetic Alterations In Lung Adenocarcinoma Manifesting As Ssnsmentioning
confidence: 99%
“…Other genetic alterations identified in lung adenocarcinoma manifesting as SSNs included KRAS mutations, HER2 mutations, BRAF mutations, ALK rearrangement, and ROS1 rearrangement (11,(53)(54)(55)(56)(57)(58).…”
Section: Genetic Alterations In Lung Adenocarcinoma Manifesting As Ssnsmentioning
confidence: 99%
“…Also of great interest is whether or not there is a correlation between the imaging characteristics of LUAD and the frequency with which it undergoes EGFR mutations. Wei et al found no link between EGFR and ground glass opacity (GGO) development, but Ortiz et al found an increased probability of EGFR mutations when GGO was present in pulmonary nodules ( 11 , 12 ). As a result, we aimed to perform a systematic review and meta-analysis of the literature to learn more about the correlation between EGFR mutations and the percentage of ground glass opacity and final histological classification in people with NSCLC.…”
Section: Introductionmentioning
confidence: 99%